2013
DOI: 10.4321/s1578-84232013000200002
|View full text |Cite
|
Sign up to set email alerts
|

Intervención Formativa con el Profesorado de Danza e Influencia Motivacional en su Alumnado

Abstract: Se diseña un programa de formación para el profesorado con el principal objetivo de evaluar si sus estudiantes mejoran sus niveles motivacionales. Integraron la muestra 5 profesores voluntarios de un Conservatorio de danza (3 del grupo experimental y 2 del grupo control), así como sus respectivos alumnos (N=60). Se evaluó antes de la intervención la conducta de instrucción mediante el CBAS (Coaching Behaviour Assessment System) adaptado a danza, así como la motivación de los alumnos a través de un Cuestionario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Research has indicated that repetitive negative comments from teachers, for instance, can lead to a decrease in dance students' perceived competence. 12 Dance teachers' messages and feedback have been found to exert an important influence on students' self-efficacy and also to directly influence their motivation. 13 In another study, Garcia-Dantas and Caracuel showed that those teachers who exhibited higher frequency of positive reinforcement had more motivated students (defined as those with a stronger desire to invest effort in training and to perfect themselves).…”
Section: The Effect Of Manipulated and Accurate Assessment Feedback O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Research has indicated that repetitive negative comments from teachers, for instance, can lead to a decrease in dance students' perceived competence. 12 Dance teachers' messages and feedback have been found to exert an important influence on students' self-efficacy and also to directly influence their motivation. 13 In another study, Garcia-Dantas and Caracuel showed that those teachers who exhibited higher frequency of positive reinforcement had more motivated students (defined as those with a stronger desire to invest effort in training and to perfect themselves).…”
Section: The Effect Of Manipulated and Accurate Assessment Feedback O...mentioning
confidence: 99%
“…13 In another study, Garcia-Dantas and Caracuel showed that those teachers who exhibited higher frequency of positive reinforcement had more motivated students (defined as those with a stronger desire to invest effort in training and to perfect themselves). 12 Teachers' feedback behavior can also influence what dancers believe they can achieve, the goals they set, and therefore the effort exerted to reach those goals. 14 These findings from past research justify further examination of teachers' feedback practices to identify the strategies and methods that promote optimal self-efficacy in dancers.…”
Section: The Effect Of Manipulated and Accurate Assessment Feedback O...mentioning
confidence: 99%
“…The younger dancers are at the end of their higher education or entering the professional world and their maximum reference are their teachers. Intervention proposals have been mentioned for improving the teaching in the staff of a professional conservatory (García-Dantas, Caracuel-Tubío, and Peñaloza-Gómez, 2013). Perhaps it would be advisable for such interventions also to be implemented in areas of higher education and professional environments, where there International Journal of Instruction, April 2020 • Vol.13, No.2 are older dancers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are very few studies on professional dance that determine the differences in psychological stress with regard to gender ( Van Winden et al, 2020 ), probably due to the low number of men who practice dance ( Ibáñez-Granados, Ortiz-Camacho & Baena-Extremera, 2018 ; Requena-Pérez, Martín-Cuadrado & Lago-Marín, 2015 ). However, some studies done with female dancers found differences in psychological stress, showing greater stress in both dance students, due to the lack of time to be able to make it compatible with their studies ( García-Dantas & Caracuel, 2011 ) and in professional dancers during their performance ( De Wet, Africa & Venter, 2022 ). Other studies indicate that professional men dancers show psychological unease that is significantly more negative than the women dancers ( Hamilton et al, 1989 ).…”
Section: Introductionmentioning
confidence: 99%